2016
DOI: 10.1016/j.molcel.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2 Puts Its Shoulder to Krebs’ Wheel

Abstract: In this issue of Molecular Cell, Moloughney et al. (2016) find that mTORC2 responds to falling levels of glucose and glutamine catabolites, promoting glutaminolysis and preserving the TCA cycle and hexosamine biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…mTORC2 is stimulated by growth factors such as insulin, insulin like growth factor (IGF), and hormones, which signal to PI3K [ 47 ]. Although both mTORC1 and mTORC2 are activated by growth factors, including insulin, the signaling mechanism of mTORC2 activation is distinct from that of mTORC1 [ 8 ].…”
Section: Regulation Of Mtorc2mentioning
confidence: 99%
“…mTORC2 is stimulated by growth factors such as insulin, insulin like growth factor (IGF), and hormones, which signal to PI3K [ 47 ]. Although both mTORC1 and mTORC2 are activated by growth factors, including insulin, the signaling mechanism of mTORC2 activation is distinct from that of mTORC1 [ 8 ].…”
Section: Regulation Of Mtorc2mentioning
confidence: 99%
“…It is also unclear what cellular signals mTORC2 might sense, or whether it is regulated through other mechanisms such as localization. Early studies indicated that mTORC2 activity is stimulated by growth factors [125127], and more recently glucose [55, 128130] and glutamine levels [131, 132]. In addition, lipid-derived signal also may control mTORC2 signaling [133, 134].…”
Section: Future Challengesmentioning
confidence: 99%
“…This study not only provides a key link between one carbon metabolism and the mTORC1 pathway but raises the question of whether additional intermediate metabolites in amino acid catabolism are also sensed by mTORC1. For example, mTORC1 has been shown to sense α-ketoglutarate, a product of glutaminolysis 91,92 .…”
Section: Amino Acid Sensors From Hypothesis To Realitymentioning
confidence: 99%
“…However, both mTOR complexes also play a critical role in regulating catabolic processes. One recently discovered activity is that both mTORC2 and mTORC1 act to promote anaplerosis – the refilling of the citric acid cycle – by promoting the formation of α-ketoglutarate from glutamine 92 . Here, we will focus on the lysosomal pathways that lie downstream of the mTOR complexes.…”
Section: Lysosomal Functions Downstream Of Mtor Complexesmentioning
confidence: 99%
See 1 more Smart Citation